Vasodilator treatment with isosorbide dinitrate and hydralazine in chronic heart failure. Issue 4 (April 1981) - Massie, B M; Kramer, B; Shen, E; Haughom, F
Abstract : Several reports have suggested that because isosorbide dinitrate and hydralazine have different and additive haemodynamic effects at rest in patients with chronic heart failure, these agents should be administered in combination. Some studies, however, indicate thay they are effective individually as well. Since most patients with heart failure are symptomatic only with activity, we examined the haemodynamic effects of these drugs given individually and in combination, at rest and during upright bicycle exercise. As has been noted previously, at rest isosorbide significantly lowered both ventricular filling pressures and did not change cardiac output; hydralazine increased cardiac output and had only a slight effect on pulmonary capillary wedge pressure; combined treatment produced both beneficial effects. In contrast, during exercise isosorbide dinitrate also raised cardiac output while hydralazine more dramatically lowered the wedge pressure. Combined treatment produced significantly greater improvement in each haemodynamic index than either drug alone, with a resulting 54 per cent increase in exercise cardiac output, and a 33 per cent reduction in exercise wedge pressure. Maximal oxygen consumption increased acutely during combined treatment. These findings suggest that isosorbide dinitrate and hydralazine may each be effective in some patients, but that they are even more beneficial in combination.